2007
DOI: 10.1038/sj.gt.3302946
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of human CD46 by adenovirus serotype 35 vectors

Abstract: Human CD46 (membrane cofactor protein), which serves as a receptor for a variety of pathogens, including strains of measles virus, human herpesvirus type 6 and Neisseria, is rapidly downregulated from the cell surface following infection by these pathogens. Here, we report that replicationincompetent adenovirus (Ad) serotype 35 (Ad35) vectors, which belong to subgroup B and recognize human CD46 as a receptor, downregulate CD46 following infection. A decline in the surface expression of CD46 in human peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Disappearance of CD46 from the cell surface through internalization is MOI dependent and reached a peak at about 8 h postinfection. Our observation is in agreement with a study by Sakurai et al, who reported downregulation of CD46 after Ad35 infection (21). Furthermore, we found that, in MO7e cells, Ad5/35 particles with higher affinity to CD46 remain longer in endosomes (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Disappearance of CD46 from the cell surface through internalization is MOI dependent and reached a peak at about 8 h postinfection. Our observation is in agreement with a study by Sakurai et al, who reported downregulation of CD46 after Ad35 infection (21). Furthermore, we found that, in MO7e cells, Ad5/35 particles with higher affinity to CD46 remain longer in endosomes (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…CD46 serves as a receptor for several pathogens including strains of measles virus (10), human herpesvirus type 6 (42), group A streptococci (38), adenovirus (13,45), and Neisseria (24). Among these pathogens, infection by certain strains of measles virus (33,43), human herpesvirus type 6 (42), serogroup B adenovirus (41), and Neisseria gonorrhoeae (15) has been shown to cause CD46 downregulation from the cell surface. The detailed mechanisms of surface CD46 downregulation upon infection by these pathogens remain to be elucidated; however, the decrease in the surface density of CD46 renders the cells more susceptible to lysis by complement, as demonstrated in vitro (44), and may contribute to the attenuation of these pathogens by the rapid clearing of infected cells.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were incubated with UV-inactivated ML from MV Edmonston strain-infected rhesus monkey kidney (RMK) cells (4 ϫ 10 5 PFU/ml, kindly provided by Steven Wesselingh, Macfarlane Burnet Institute for Medical Research, Melbourne, Australia [12]) or control RMK cell lysate alone, for 24 h as previously described (25), or with PHA (1 g/ml; Murex Biotech, Kent, United Kingdom) for 48 h. The data were acquired using a FACSCalibur flow cytometer and analyzed by using CellQuest (BD Biosciences) and FlowJo software (Tree Star, Ashland, OR). The percent CD46 downregulation after ML or PHA stimulation was calculated using the method of Sakurai et al (26).…”
Section: Methodsmentioning
confidence: 99%